2019
DOI: 10.1080/17453674.2019.1604343
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes in hip resurfacing versus conventional total hip arthroplasty: a register-based matched cohort study of 726 patients

Abstract: Background and purpose — The theoretical mechanical advantages of metal-on-metal hip resurfacing (MoM-HR) compared with conventional total hip arthroplasty (THA) have been questioned. Studies including measures of patient-reported function, physical activity, or health-related quality of life have been sparse. We compared patient-reported outcomes in MoM-HR patients with a matched group of patients with conventional THA at 7 years post-surgery. Patients and methods — Patients and patient data were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
2
10
0
2
Order By: Relevance
“…A 20-points mean difference was seen in the HOOS-PS in favor of HRA. This is in accordance with a recent publication of Oxblom et al ( 2019 ). They studied 726 subjects 7 years after primary HRA or conventional THA showing a significant difference in HOOS subscales of function of daily living and function in sport and recreation, although HOOS subscales of symptoms, pain, and quality of life, EQ-5D index, and visual analog scores for pain and satisfaction did not differ.…”
Section: Discussionsupporting
confidence: 94%
“…A 20-points mean difference was seen in the HOOS-PS in favor of HRA. This is in accordance with a recent publication of Oxblom et al ( 2019 ). They studied 726 subjects 7 years after primary HRA or conventional THA showing a significant difference in HOOS subscales of function of daily living and function in sport and recreation, although HOOS subscales of symptoms, pain, and quality of life, EQ-5D index, and visual analog scores for pain and satisfaction did not differ.…”
Section: Discussionsupporting
confidence: 94%
“…19 There is presently some suggestion that dual mobility articulations should be offered as a mainstream alternative to more traditional articulations. 20 Given the advantageous and well-established increase in stability associated with a dual mobility articulation, 4,5 the trend for increased utilisation of the technology may be related to increasing recognition of the relevance of unfavourable spinopelvic mobility and its implications in the stability of total hip arthroplasty. There has also been growth of their use in high risk groups such as those with neuromuscular conditions or cognitive impairment.…”
Section: Dual Mobility Total Hip Arthroplastymentioning
confidence: 99%
“…The present study was in accordance, and no statistically significant differences were observed in HOOS Pain or HOOS-PS between HR and THA at 1-year follow-up. An Oxblom et al study 20 differed from the rest: statistically higher HOOS ADL and sports and recreation subscales were observed in the HR group. This was a retrospective review of 299 HRs compared with 270 THAs at a mean follow-up of 7 years.…”
Section: Discussionmentioning
confidence: 83%